Profiles and Pauses: Two Practical Activities for the Writing Class - Ernest Hall (TEFLIN Journal: A publication on the teaching and learning of English, 1998)
Abstract : This article describes two classroom activities, "Profiling" and "Pause Analysis", that can be successfully used in ESL writing classes. "Profiling" addresses such problems as poor development of ideas, simplistic ideas, and lack of coherence in written texts. "Pause Analysis" focusses on the thinking processes that students engage in while drafting text, processes such as searching for ideas, evaluatÃÂing ideas, and postponing ideas. Both activities enable the instructor to assume the role of intervener in the students writing processes, rather than evaluator of the text produced. In drawing The attention of the student write to both product and process, "Profiling" and "Pause Analysis" help them develop an awareness of the relation-ship between ideas in English expository text and the thinking proÃÂcesses that writers engage in while drafting such text.